New rinderpest vaccine - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
A new vaccine that could rid Africa of rinderpest is ready for field trials in East and West Africa. At present the vaccine used against rinderpest is the Plowright vaccine, but it is expensive and difficult to make, needs a veterinarian to...